New Peptides as Potential Players in the Crosstalk Between the Brain and Obesity, Metabolic and Cardiovascular Diseases - Czerwińska, Magdalena; Czarzasta, Katarzyna; Cudnoch-Jędrzejewska, Agnieszka (Frontiers in Physiology, 2021)
According to the World Health Organization report published in 2016, 650 million people worldwide suffer from obesity, almost three times more than in 1975. Obesity is defined as excessive fat accumulation which may impair health with non-communicable diseases such as diabetes, cardiovascular diseases (hypertension, coronary artery disease, stroke), and some cancers. Despite medical advances, cardiovascular complications are still the leading causes of death arising from obesity. Excessive fat accumulation is caused by the imbalance between energy intake and expenditure. The pathogenesis of this process is complex and not fully understood, but current research is focused on the role of the complex crosstalk between central nervous system (CNS), neuroendocrine and immune system including autonomic nervous system, adipose tissue, digestive and cardiovascular systems. Additionally, special attention has been paid to newly discovered substances: neuropeptide 26RFa, preptin, adropin. It was shown that the above peptides are synthesized both in numerous structures of the CNS and in many peripheral organs and tissues, such as the heart, adipose tissue and the gastrointestinal tract. Recently, particular attention has been paid to the role of the presented peptides in the pathogenesis of obesity, metabolic and cardiovascular system diseases. The aim of this review is to summarize the role of newly investigated peptides in crosstalk between brain and peripheral organs in the pathogenesis of obesity, metabolic and cardiovascular diseases.